PENDEKATAN EVALUASI PEMBELAJARAN BERDASARKAN HADIS TARBAWI: ANALISIS KUALITATIF HERMENEUTIK - Tri Yugo; Helmi Aziz; Alhamuddin (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2024)
This study aims to analyze the principle of learning evaluation from the perspective of the tarbawi hadith, focusing on two hadiths narrated by Tirmidhi (Number 278) and Bukhori (Number 401). This study uses a descriptive-analytical qualitative method with a hermeneutic approach to explore the educational values contained in these hadiths. Through in-depth analysis, the study found that the evaluation principles contained in the hadith, such as direct observation, formative feedback, repetition for improvement, and individualized approaches, are highly relevant to contemporary learning practices. The study results show that the tarbawi values contained in these hadiths can be implemented in modern education, especially in building a personalized learning approach based on spiritual, moral, and academic values. This study also concludes that the hadith evaluation principle focuses on cognitive aspects and students' affective and psychomotor aspects, which are relevant for shaping holistic character and competence. Thus, this research is expected to contribute to the development of Islamic education theory and increase the effectiveness of learning evaluation in modern education.